2015
DOI: 10.1021/jp5109152
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption and Dissociation at Metal-Supported Ceria Thin Films: Thickness and Interface-Proximity Effects Studied with DFT+U Calculations

Abstract: The chemistry of several catalytic processes can be controlled by tuning metal−oxide interfaces, as demonstrated by fundamental studies on inverse model catalysts. We investigate the effects of the metal−oxide interface on the surface reactivity of ceria (CeO 2 ) thin films supported by a copper metal surface. Our density functional theory (DFT+U) calculations reveal that the interface has impact on the surface water adsorption and dissociation when the thickness of the ceria film is below ≈9 Å. On thinner fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…One example we will discuss in this review is the spontaneous water dissociation at the water/CeO 2 (111) interface 177 . Farnesi Camellone et al designed a CeO 2 surface with a Pt 6 cluster on it.…”
Section: Applications Of Simulations With Other Oxide Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…One example we will discuss in this review is the spontaneous water dissociation at the water/CeO 2 (111) interface 177 . Farnesi Camellone et al designed a CeO 2 surface with a Pt 6 cluster on it.…”
Section: Applications Of Simulations With Other Oxide Interfacesmentioning
confidence: 99%
“…176 One example we will discuss in this review is the spontaneous water dissociation at the water/CeO 2 (111) interface. 177 Farnesi Camellone et al designed a CeO 2 surface with a Pt 6 cluster on it. They found that after a proton transfer to the CeO 2 surface, the resulting OH À binds to a Pt site instead of the Ce site.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…101,141,142 DFT calculations were employed to investigate water dissociation at the ceria (111) surface 143 and at the ceria/liquid interface 144 as well as to elucidate the charge transfers between Pt particles and the ceria support resulting from water dissociation. The influence of the aqueous environment on the reaction mechanism, thermodynamics and kinetics was investigated by means of ab initio molecular dynamics (MD) simulations.…”
Section: Charge Transfer In Aqueous Environmentsmentioning
confidence: 99%
“…[24,25] Significantp rogress has been achieved in understandingw ater adsorption behavior on cleanC eO 2 (111)s urfaces. [26][27][28][29][30][31][32][33][34][35][36][37][38] For example, noncontact atomic force microscopy (nc-AFM)e xperiments by Gritschneder et al [29] and the lowtemperature scanning tunneling microscopy (STM) experiments by Grinter et al [31] suggested that water did not undergo complete dissociation on clean cerias urfaces. The calculations showed molecular water adsorption on the top site of surfaceC ea toms was the most thermodynamically stable structure.…”
Section: Introductionmentioning
confidence: 99%
“…The CeO 2 (111) surface is the most thermodynamically stable surface . Significant progress has been achieved in understanding water adsorption behavior on clean CeO 2 (111) surfaces . For example, noncontact atomic force microscopy (nc‐AFM) experiments by Gritschneder et al .…”
Section: Introductionmentioning
confidence: 99%